2009
DOI: 10.1021/la901049h
|View full text |Cite
|
Sign up to set email alerts
|

Latex Imaging by Environmental STEM: Application to the Study of the Surfactant Outcome in Hybrid Alkyd/Acrylate Systems

Abstract: Among other uses, latexes are a successful alternative to solvent-borne binders for coatings. Efforts are made to produce hybrid nanostructured latexes containing an acrylic phase and an alkyd phase. However, after the film-forming process, the surfactant used to stabilize these latexes remains in the film, and its location can have a drastic effect on the application properties. Among the processing parameters, the alkyd hydrophobicity can strongly influence this location. This article aims at the imaging of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…It is thus attributed to Triton, in agreement with the observations of Faucheu et al . () on other latex formulations. From the measurement on 233 particles, the median value of the distance between centroids is equal to 237 nm, which is also similar to the value measured on SBA alone, the slight difference being possibly attributed to a slightly different local concentration of latex particles.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…It is thus attributed to Triton, in agreement with the observations of Faucheu et al . () on other latex formulations. From the measurement on 233 particles, the median value of the distance between centroids is equal to 237 nm, which is also similar to the value measured on SBA alone, the slight difference being possibly attributed to a slightly different local concentration of latex particles.…”
Section: Resultssupporting
confidence: 94%
“…The SBA particles are surrounded by a uniform bright layer. The existence of such a shell has been previously reported and can be assigned to PMMA (Faucheu et al ., ), although such contrast could not be modelled by Monte Carlo simulations (not shown). By image analysis on 127 particles, it has been found that the diameter of the SBA core – without the PMMA shell – follows a Gaussian distribution; see the blue curve in Figure , with an average value of 171 ± 4 nm.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The SBA particles has already included 3% PMMA shell playing the role of steric surfactant. Some other surfactants can also be introduced to further stabilize the latex for some special applications [4].In this work, we show series of tilted images that are acquired during in situ hydration / dehydration experiments with our improved device. Reconstructed volumes are obtained using the image processing software Etomo and ImageJ (see Figure 1), and the resolution is calculated using Fourier Shell Correlation (FSC).…”
mentioning
confidence: 99%
“…The SBA particles has already included 3% PMMA shell playing the role of steric surfactant. Some other surfactants can also be introduced to further stabilize the latex for some special applications [4].…”
mentioning
confidence: 99%